Pengaruh Indikator Makro Sosial-Ekonomi Terhadap Kemiskinan di Kalimantan Tengah - Rahman, Abdul (PT Maju Malaqbi Makkarana, 2025)
Poverty alleviation is still a major challenge in regional development, including in Central Kalimantan Province. This study aims to analyze the effect of Gross Regional Domestic Product (GRDP), Human Development Index (HDI), and population on poverty rates at the district/city level in Central Kalimantan Province during the 2019–2023 period. This study uses a quantitative approach with panel data analyzed using a fixed effect regression model and the Hausman test to select the best model. The results of the analysis show that the GRDP variable has a positive and significant effect on poverty rates. This means that an increase in GRDP does not necessarily reduce poverty, which can be caused by inequality in income distribution or concentration of growth in the non-pro-poor sector. On the other hand, the HDI and population variables do not have a significant effect on poverty rates in the observed period. These findings indicate the need for an evaluation of the direction and equity of development, as well as the importance of strengthening policies that directly target poor groups. In conclusion, economic growth in Central Kalimantan has not been inclusive in reducing poverty, so development strategies need to be more pro-vulnerable.